Contrasting thermoresponsiveness of stereoisomers of a dense 1,2,3-triazole polymer carrying amide side chains - Okuno, Koji; Miura, Junji; Yamasaki, Shota; Nakahata, Masaki; Kamon, Yuri; Hashidzume, Akihito (Polymer Chemistry, 2023)
Since thermoresponsive polymers are an important class of smart polymer materials, it is an important subject of investigation to develop thermoresponsive polymers with a new polymer backbone for expanding their potential. Recently, we synthesized poly( N -ethyl- N -methyl-4-azido-5-hexynamide) (poly( ME )) by copper( i )-catalyzed azide-alkyne cycloaddition (CuAAC) polymerization as a new lower-critical-solution-temperature (LCST) type thermoresponsive polymer. In this study, we synthesized two types of stereoregular poly( ME ) ( i.e. , isotactic and syndiotactic) by CuAAC polymerization of ME dimers of the R - and R -isomers, and the R - and S -isomers, respectively, and investigated their thermoresponsive behavior. Binary mixtures of isotactic poly( ME ) ( iso -poly( ME )) with dimethyl sulfoxide (DMSO) and with N , N -dimethylformamide (DMF) underwent thermoresponsive gel-to-sol transition, in which the mixture turned from gel to sol at a certain temperature as the temperature was increased. On the other hand, aqueous solutions of syndiotactic poly( ME ) ( syndio -poly( ME )) underwent the LCST-type phase transition, in which the solution was transparent at lower temperatures whereas it became turbid at a certain temperature as the temperature was increased. Thermoresponsive behavior of stereoisomers of a dense triazole polymer was studied; mixtures of the isotactic one underwent thermoresponsive gel-to-sol transition, and aqueous solutions of the syndiotactic one underwent LCST-type phase transition.